2006
DOI: 10.1186/1741-7007-4-23
|View full text |Cite
|
Sign up to set email alerts
|

Early cortical facilitation for emotionally arousing targets during the attentional blink

Abstract: Background: The present study aimed to investigate the time course of electrocortical facilitation for affectively arousing written words during the so-called 'attentional blink' (AB) period in a rapid serial visual presentation (RSVP) task. The AB refers to a period of reduced awareness for secondtarget stimuli following a first target by an interval of about 200-500 ms. Pleasant, neutral, and unpleasant written verbs were used as second targets in an 8.6-Hz RSVP paradigm that contained affectively neutral wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
60
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 54 publications
6
60
0
3
Order By: Relevance
“…This method has been used in some AB studies (Kranczioch et al, 2007; Slagter, Lutz, Greischar, Nieuwenhuis, & Davidson, 2009). Other studies restricted their analysis to only one predefined frequency, in which case a very effective way of amplitude extraction is complex demodulation (Keil & Heim, 2009; Keil, Ihssen, & Heim, 2006). In complex demodulation, a sine and cosine function at a frequency of interest (FOI) are multiplied with the data.…”
Section: Some Basics On Oscillatory Brain Activitymentioning
confidence: 99%
“…This method has been used in some AB studies (Kranczioch et al, 2007; Slagter, Lutz, Greischar, Nieuwenhuis, & Davidson, 2009). Other studies restricted their analysis to only one predefined frequency, in which case a very effective way of amplitude extraction is complex demodulation (Keil & Heim, 2009; Keil, Ihssen, & Heim, 2006). In complex demodulation, a sine and cosine function at a frequency of interest (FOI) are multiplied with the data.…”
Section: Some Basics On Oscillatory Brain Activitymentioning
confidence: 99%
“…Emotional stimuli relative to other visual stimuli are assumed to have competitive advantages due to their intrinsic stimulus significance. A number of studies using different experimental paradigms, including attentional blink (Anderson and Phelps, 2001;Keil and Ihssen, 2004;Keil et al, 2006) and visual search tasks (Öhman et al, 2001a,b) demonstrated the capacity of emotional stimuli to rapidly and involuntarily draw attention. Further evidence came from event-related potential (ERP) studies which reported emotion-specific amplitude modulations of early and late components (Cuthbert et al, 2000;Junghöfer et al, 2001;Schupp et al, 2004b) and from functional magnetic resonance imaging (fMRI) studies where emotional arousing stimuli elicited increased activation in occipital and inferior temporal cortical areas (Junghöfer et al, 2006;Sabatinelli et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The suggestions extant in the literature are somewhat inconsistent. For instance, Keil, Ihssen, and Heim (2006) suggested that the processing stages that may be modulated by emotion include several possible Herbert, Junghöfer, & Kissler, 2008;Kissler, Herbert, Peyk, & Junghöfer, 2007;Kissler, Herbert, Winkler, & Junghöfer, 2009;see Kissler, Assadolahi, & Herbert, 2006, for a review of heterogeneous evidence of early effects) and LPC modulations (e.g., Fischler & Bradley, 2006;Herbert, Kissler, Junghöfer, Peyk, & Rockstroh, 2006;Naumann, Bartussek, Diedrich, & Laufer, 1992;. Since these effects were found even in silent reading tasks, which do not require any overt decisions on the words, the emotional valence of a word may be processed automatically.…”
mentioning
confidence: 99%
“…In contrast to most of the previous studies of emotion effects on ERPs during word processing, we used verbs rather than nouns or adjectives. Verbs differ from other word classes by their very direct reference to actions and have been shown to elicit emotional effects in the attentional blink paradigm (Keil & Ihssen, 2004;Keil et al, 2006). Experiment 1 employed a lexical decision task (LDT) on emotionally positive, negative, and neutral single verbs.…”
mentioning
confidence: 99%